2013
DOI: 10.1021/jz400360v
|View full text |Cite
|
Sign up to set email alerts
|

More Is Different: Experimental Results on the Effect of Biomolecules on the Dynamics of Hydration Water

Abstract: Biological interfaces characterized by a complex mixture of hydrophobic, hydrophilic, or charged moieties interfere with the cooperative rearrangement of the hydrogen-bond network of water. In the present study, this solute-induced dynamical perturbation is investigated by extended frequency range depolarized light scattering experiments on an aqueous solution of a variety of systems of different nature and complexity such as small hydrophobic and hydrophilic molecules, amino acids, dipeptides, and proteins. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 36 publications
17
94
0
Order By: Relevance
“…Molecular dynamics (MD) simulations (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and other experimental approaches (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) have revealed the protein is surrounded by dynamically retarded hydration water, with the innermost shell having a density higher than that of bulk water. However, even today, experimentally characterizing the dynamics and the structure of the water HB network in this hydration shell is challenging, because the water-water HB lifetime is very short (typically 1 ps) (38).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulations (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and other experimental approaches (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) have revealed the protein is surrounded by dynamically retarded hydration water, with the innermost shell having a density higher than that of bulk water. However, even today, experimentally characterizing the dynamics and the structure of the water HB network in this hydration shell is challenging, because the water-water HB lifetime is very short (typically 1 ps) (38).…”
Section: Introductionmentioning
confidence: 99%
“…However, even today, experimentally characterizing the dynamics and the structure of the water HB network in this hydration shell is challenging, because the water-water HB lifetime is very short (typically 1 ps) (38). To observe directly the HB dynamics and structure fluctuating at subpicosecond to picosecond timescales, depolarized light scattering (DLS) (33,34), optical Kerr effect (OKE) spectroscopy (35), incoherent neutron scattering (INS) spectroscopy (36), and Brillouin spectroscopy (37) were developed, but they all have experimental limitations. DLS and OKE probe weak second-order optical processes, and INS and Brillouin spectroscopy require isotopic substitution, which may alter the native water HB network, if only weakly.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] These heterogeneously polarized, heterogeneously compressed, [17][18][19] and potentially mutually frustrated interfacial water domains merge into an interfacial sub-ensemble involving several hundreds of water molecules, with its properties quite distinct from the bulk. 20,21 The bulk perspective does not apply just to the protein part of the thermal bath, but to the hydration shell as well.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The influence of small and large molecules on the surrounding solvent molecules has been described in terms of both destructuring/restructuring effects on the whole HB assembly of water molecules 16 and change in the local dynamics of the solvent at different chemical sites. [17][18][19][20] Recently, we used oligosaccharide based hydrogels as model systems to study the effect on the HB dynamics of water [21][22][23][24] of two factors, i.e. (i) the nano-scale confinement of water and (ii) the presence of hydrophobic/hydrophilic portions at the interface with the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…IR and Raman spectroscopy can be conveniently employed for the quantitative evaluation of the extent of perturbation on water organization due to the combination of confinement effects 3,4,[6][7][8] and interactions with hydrophobic/ hydrophilic portions of the confining polymeric matrix. [15][16][17]19 In the past few years, it was shown that the combination of UV-Raman scattering experiments and FT-IR spectroscopy is a simple strategy to separate the spectral response arising from the polymer matrix and the water molecules. [21][22][23][24] The separate analysis of the vibrational dynamics associated with confined water molecules and the polymer skeleton thus provides new insights into the interplay of different types of HB interactions that coexist in hydrogel phases.…”
Section: Introductionmentioning
confidence: 99%